Lyceum Guild: Promoting Informal Learning in the African American Community - E. Paulette Isaac (Adult Education Research Conference, 2008)
The purpose of this historical study was to examine informal learning of African Americans in the context of the African American church. Three themes were identified.
Keywords: African Americans; African American Church; Informal Learning; Learning Contexts; Nonformal Learning